2021
DOI: 10.1128/spectrum.02183-21
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus in Substrates for Black Soldier Fly Larvae (Hermetia illucens) and Its Dynamics during Rearing

Abstract: Given the increasing need for (more sustainable) methods to upcycle organic waste streams, the interest to rear insects, like black soldier fly larvae (BSFL), on such streams is increasing. This study reveals that S. aureus is abundantly present in such waste streams, which might be a point of attention for insect producers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 89 publications
1
42
1
Order By: Relevance
“…To improve connectivity and specialization, the ideal and minimal transport conditions for insect eggs are studied. Finally, new opportunities are sought to expand the commercialization of insect rearing by-products [ 22 , 23 ].…”
Section: Project Contribution Beyond the State-of-the-artmentioning
confidence: 99%
See 1 more Smart Citation
“…To improve connectivity and specialization, the ideal and minimal transport conditions for insect eggs are studied. Finally, new opportunities are sought to expand the commercialization of insect rearing by-products [ 22 , 23 ].…”
Section: Project Contribution Beyond the State-of-the-artmentioning
confidence: 99%
“…These include plant toxins in BSF and MW, and the pathogens Salmonella spp., Staphylococcus aureus, Bacillus cereus s.l., and Clostridium perfringens in BSF and/or MW. The first studies on the transmission of pathogens to larvae of edible insects from the substrate have recently been published [22,51,52] and additional studies are currently ongoing. The capacity of insects to metabolize mycotoxin is also being studied in greater depth [53], covering several mycotoxins in BSF and MW.…”
Section: Control Insect Safetymentioning
confidence: 99%
“…The high relative abundance of Basidiomycota in BR compared to CC can almost exclusively be attributed to members of the most abundant genus Trichosporon , which has been identified previously in BSFL guts ( Tanga et al, 2021 ) and as the dominant basidiomycetous genus in substrates exposed to BSFL ( Bernard et al, 2020 ). Indeed, BSFL were suggested to associate with the genus to suppress pathogenic bacteria in the rearing environment of the larvae ( Gorrens et al, 2021 ). Trichosporon has been reported to degrade aromatic compounds such as phenols ( Middelhoven, 1993 ; DeRito and Madsen, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown a reduction in the populations of several strains of S. aureus over time in organic substrates inhabited by BSFL ( 6 , 13 ). However, to the best of our knowledge, no information is currently available on this topic regarding MRSA, despite its importance to public health ( 13 ).…”
Section: Introductionmentioning
confidence: 96%
“…( 10 , 12 ). Evidence indicating BSFL suppression of Gram-positive species at the in vivo level is an emerging topic ( 10 , 13 ).…”
Section: Introductionmentioning
confidence: 99%